2022
DOI: 10.1111/jbg.12753
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal and Z‐linked genetic evaluation for body weight in Mazandaran native chicken using different models for dosage compensation on the Z chromosome

Abstract: The objectives of this study were to assess the autosomal and sex-linked genetic inheritance of growth traits and identify the effective dosage compensation on the Z chromosome in Mazandaran native chickens. The data included body weights at hatching (BW0), 8 weeks (BW8) and 12 weeks (BW12) of age, related to the first 21 generations of selection, were collected from Mazandaran native chicken breeding centre. The fixed effects included sex of birds in two classes, hatch in five classes and generation in 21 cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…We found no significant contribution of the covariance between direct and maternal genetic effects to the studied traits. Several studies have reported negative direct‐maternal genetic covariance to be significant (Gholizadeh & Hafezian, 2022; Kaviani et al., 2023). The negative direct‐maternal genetic covariance can be caused by the negative direct‐maternal environmental covariance which is usually neglected in genetic evaluation (Robinson, 1996) maybe because the environmental covariance is not straightforward to include in the genetic models using common software.…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant contribution of the covariance between direct and maternal genetic effects to the studied traits. Several studies have reported negative direct‐maternal genetic covariance to be significant (Gholizadeh & Hafezian, 2022; Kaviani et al., 2023). The negative direct‐maternal genetic covariance can be caused by the negative direct‐maternal environmental covariance which is usually neglected in genetic evaluation (Robinson, 1996) maybe because the environmental covariance is not straightforward to include in the genetic models using common software.…”
Section: Discussionmentioning
confidence: 99%